Public Debt Dynamics in Nepal: Balancing Economic Growth and Institutional Governance - Adhikari, Gyan Mani; Chhetri, Santosh; Rai, Hemanta; Karki, Padam; Shreshtha, Jamuna (Nepal Journal of Multidisciplinary Research, 2025)
Background: Nepal faces complex public debt management challenges amid its transition to federalism, post-earthquake reconstruction, and pandemic recovery. With public debt reaching 41.5 percent of GDP by 2021/22 from 25 percent in 2015/16, understanding the interplay between institutional governance and debt dynamics is crucial for fiscal sustainability. Methods: This study employs the Autoregressive Distributed Lag (ARDL) approach on time series data spanning 1996-2023 to analyze relationships between governance indicators, economic growth, remittances, trade balance, and Nepal's debt-to-GDP ratio. The model incorporates bounds testing to establish cointegration and error correction mechanisms to capture adjustment dynamics. Results: Governance indicators demonstrate a significant positive relationship with debt levels, suggesting initial institutional reforms may require increased borrowing. Remittances and trade balance exhibit strong negative relationships with public debt, indicating their role as alternative financing sources and debt reduction pathways. The error correction model confirms rapid adjustment to equilibrium, validating relationship stability. Conclusion: While institutional governance improvements may initially necessitate higher debt levels, strategic management of remittances and trade balance presents viable debt reduction pathways. Policy recommendations include strengthening governance frameworks, optimizing remittance flows, diversifying trade, and implementing targeted debt management strategies tailored to Nepal's evolving federal structure. Novelty: This research uniquely integrates institutional governance metrics with remittance flows and trade dynamics to provide a comprehensive analysis of debt determinants in Nepal's specific context, offering empirically-grounded policy pathways for balancing development with fiscal sustainability.